Relative neuroprotective effects hyperbaric oxygen treatment and TLR4 knockout in a mouse model of temporary middle cerebral artery occlusion. (1st February 2016) - Pushkov, Dennis; Nicholson, James D.; Michowiz, Shalom; Novitzky, Ivan; Weiss, Shirel; Ben Hemou, Moshe; Hochhauser, Edith; Goldenberg-Cohen, Nitza
Abstract : Purpose: To examine the effects of hyperbaric oxygen (HBO) therapy and knockout of toll-like receptor 4 (TLR4) on the outcome of temporary middle cerebral artery occlusion (MCAO) in a mouse model. Materials and Methods: MCAO was induced in anesthetized male C57Bl/6 mice (WT) and TLR4 knockout mice (TLR4 −/− ) using an intra-arterial filament method. After 30 or 90 min, the filament was removed, and the mice were given either no treatment (WT and TLR4 −/- groups) or HBO (WT only). Mice were euthanized 24 h after MCAO, and the brain infarct area was examined using 2, 3, 5-triphenyltetrazolium chloride (TTC) staining. Results: In the WT group, without treatment, lesion volume was 120 ± 13 mm 3 in the mice subjected to 30 min' MCAO and 173 ± 23 mm 3 in the mice subjected to 90 min' MCAO. Respective values with HBO treatment were 66.5 ± 36.7 mm 3 and 53.2 ± 17.2 mm 3 . The difference was significant only for 90-minute MCAO ( p < 0.01, nonparametric test). In the TLR4 −/− group (all untreated), lesion volume was 95.9 ± 17.9 after 90 min of MCAO, which was significantly lower than in the untreated WT animals ( p < 0.05, nonparametric test). Conclusions: A single treatment of HBO immediately after MCAO followed by 24 h' reperfusion significantly reduces edema and may improve perfusion. TLR4 knockout protects mice from MCAO damage, but to a lesser extent than HBO treatment.